Shared Decision-Making and Patient-Reported Outcome Measures in Valvular Heart Disease - Saeed, Sahrai; Skaar, Elisabeth; Romarheim, Andrea; Chambers, John B.; Bleie, Øyvind (Frontiers in Cardiovascular Medicine, 2022)
Patient-centered health care emphasizes shared decision-making (SDM), incorporating both clinical evidence and patient preferences and values. SDM is important in heart valve disease, both because there might be more than one treatment option and due to the importance of adherence after intervention. We aimed to describe patient information and involvement in decision-making about care and recording of patient-reported outcome measures (PROMs) in valve interventions. The opinion piece and recommendations are based upon literature review and our own experience from specialist valve clinics. Before a valve intervention, adequate patient information, discussion of the various treatment options and exploring patient preferences, in line with the concept of SDM, may improve post-intervention quality of life. After intervention, patients with prosthetic heart valves require adequate counseling and close follow-up to make them more confident and competent to manage their own health, as well as to maintain the efficacy of treatment provided. PROMs inform SDM before and improve care after valve intervention, focusing on outcomes beyond mortality and morbidity. SDM may improve post-intervention quality of life. Formal PROMs questionnaires inform SDM, quantify patient centered changes and should be used more often in clinical practice and research. A thorough assessment of baseline frailty status in patients scheduled for valve intervention is essential and may affect postoperative outcome.